Imaging the house - Wang, Shu (Lars Müller Publishers, 2012)
Wang Shu was awarded the Pritzker Prize 2012. Shu's design process always begins with an intense study of the location. The architect spends as long as possible on the site, absorbing its atmosphere. He then produces drafts in the form of hand-drawn sketches, creating them in relatively quick succession. Imagining the House follows this process in various buildings. Photographic documentation of the locations elucidate Shu's on-site research. The reproductions of drawings in this book demonstrate how the designs change and become more concrete over the course of the process. The book provides unique insights into the work of an architect who has hitherto received little attention in Europe, thereby addressing a considerable omission in the publishing world.